The origins of collective decision making - Blunden, Andy (Studies in critical social sciences, 2016)
In The Origins of Collective Decision Making, Andy Blunden identifies three paradigms of collective decision making - Counsel, Majority and Consensus, discovers their origins in traditional, medieval and modern times, and traces their evolution over centuries up to the present. The study reveals that these three paradigms have an ethical foundation, deeply rooted in historical experiences. The narrative takes the reader into the very moments when individual leaders and organisers made the crucial developments in white heat of critical moments in history, such as the English Revolution of the 1640s, the Chartist Movement of the 1840s and the early Civil Rights Movement of the 1960s. This history provides a valuable resource for resolving current social movement conflict over decision making.